Electromyographic analysis of muscle activation during pull-up variations - Dickie, J. A.; Faulkner, J. A.; Barnes, M. J.; Lark, S. D. (Journal of Electromyography and Kinesiology, 2017)
This study sought to identify any differences in peak muscle activation (EMGPEAK) or average rectified variable muscle activation (EMGARV) during supinated grip, pronated grip, neutral grip and rope pull-up exercises. Nineteen strength trained males (24.9 ± 5 y; 1.78 ± 0.74 m; 81.3 ± 11.3 kg; 22.7 ± 2.5 kg m-2) volunteered to participate in the study. Surface electromyography (EMG) was collected from eight shoulder-arm-forearm complex muscles. All muscle activation was expressed as a percentage of maximum voluntary isometric contraction (%MVIC). Over a full repetition, the pronated grip resulted in significantly greater EMGPEAK (60.1 ± 22.5 vs. 37.1 ± 13.1%MVIC; P = 0.004; Effect Size [ES; Cohen`s d] = 1.19) and EMGARV (48.0 ± 21.2 vs. 27.4 ± 10.7%MVIC; P = 0.001; ES = 1.29) of the middle trapezius when compared to the neutral grip pull-up. The concentric phases of each pull-up variation resulted in significantly greater EMGARV of the brachioradialis, biceps brachii, and pectoralis major in comparison to the eccentric phases (P = <0.01). Results indicate that EMGPEAK and EMGARV of the shoulder-arm-forearm complex during complete repetitions of pull-up variants are similar despite varying hand orientations; however, differences exist between concentric and eccentric phases of each pull-up.